PENGARUH MENEJEMEN OPERASIONAL DAN DISIPLIN KERJA TERHADAP KINERJA GURU DI SMKN 1 PROBOLINGGO - Farhan, Ainul; Ibadil Maula, Farij (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the suboptimal teacher performance observed at SMKN 1 Probolinggo, which is influenced by the complexity of vocational school operations and issues related to work discipline. Ineffective operational management, such as unclear task distribution and inefficient scheduling, along with inconsistent teacher discipline, have contributed to reduced teaching effectiveness. Therefore, this study aims to examine and analyze the influence of operational management and work discipline, both partially and simultaneously, on teacher performance.This research employs a quantitative method with a causal-associative approach. Data were collected through questionnaires distributed to teachers at SMKN 1 Probolinggo. The analysis techniques include validity and reliability tests, classical assumption tests, and multiple linear regression analysisThe results indicate that operational management has a positive and significant effect on teacher performance. Likewise, work discipline also has a positive and significant influence and acts as a key factor in enhancing teacher professionalism. Simultaneously, operational management and work discipline have a strong and significant effect on teacher performance, with a contribution (Adjusted R Square) of 61%. These findings suggest that optimal teacher performance is achieved through the synergy between effective operational management and strong individual discipline. In conclusion, improving teacher performance requires strengthening school operational systems and fostering a culture of discipline among teachers. These findings provide practical implications for school management in enhancing educational quality